A global response to a global problem: the epidemic of overnutrition - Chopra Mickey; Galbraith Sarah; Darnton-Hill Ian (The World Health Organization, 2002)
It is estimated that by 2020 two-thirds of the global burden of disease will be attributable to chronic noncommunicable diseases, most of them strongly associated with diet. The nutrition transition towards refined foods, foods of animal origin, and increased fats plays a major role in the current global epidemics of obesity, diabetes and cardiovascular diseases, among other noncommunicable conditions. Sedentary lifestyles and the use of tobacco are also significant risk factors. The epidemics cannot be ended simply by encouraging people to reduce their risk factors and adopt healthier lifestyles, although such encouragement is undoubtedly beneficial if the targeted people can respond. Unfortunately, increasingly obesogenic environments, reinforced by many of the cultural changes associated with globalization, make even the adoption of healthy lifestyles, especially by children and adolescents, more and more difficult. The present paper examines some possible mechanisms for, and WHO's role in, the development of a coordinated global strategy on diet, physical activity and health. The situation presents many countries with unmanageable costs. At the same time there are often continuing problems of undernutrition. A concerted multisectoral approach, involving the use of policy, education and trade mechanisms, is necessary to address these matters.